Diseño de un modelo de desarrollo de competencias de liderazgo para los altos mandos de una empresa de producción - Herrera Peñaherrera, Cristhian Rodrigo (2018)
The main aim of this development project is to elaborate a leadership skills development model for the senior members of a manufacturing company. Therefore, it is a crosssectional and non-experimental analysis that uses an exploratory and descriptive approach as well as being qualitative and quantitative. The development project was carried out with a sample of 36 employees who perform their activities as leaders, bosses and managers in the company ECUATRAN S.A., and who were evaluated by the application of Peter Northouse’s Leadership Skills Questionnaire, an instrument that made it possible to identify leadership skills and provide a profile of them. Through the findings, it was possible to determine the areas that need to be strengthened, and consequently elaborate the aforementioned leadership skills development model which was based on providing support tools for the company’s different job positions in detailing the 5PM Model, the GROW Model and the School of Leaders/Organizational Communication, which are useful for reaching an ideal level of managing staff in the development of the skills of each of the employees who have the top management positions within the organization.